Diversity of Alkylproline Moieties in Pyrrolobenzodiazepines Arises from Postcondensation Modifications of a Unified Building Block - Kamenik, Zdenek; Kadlcik, Stanislav; Gazak, Radek; Vobruba, Simon; Palanova, Lucie; Kuzma, Marek; Janata, Jiri (ACS chemical biology, 2017)
Anticancer pyrrolobenzodiazepines (PBDs) are one of several groups of natural products that contain unusual 4-alkyl-l-proline derivatives (APDs) in their structure. APD moieties of PBDs are characterized by high structural diversity achieved through unknown biosynthetic machinery. Based on LC-MS analysis of culture broths, feeding experiments, and protein assays, we show that APDs are not incorporated into PBDs in their final form as was previously hypothesized. Instead, a uniform building block, 4-propylidene-l-proline or 4-ethylidene-l-proline, enters the condensation reaction. The subsequent postcondensation steps are initiated by the introduction of an additional double bond catalyzed by a FAD-dependent oxidoreductase, which we demonstrated with Orf7 from anthramycin biosynthesis. The resulting double bond arrangement presumably represents a prerequisite for further modifications of the APD moieties. Our study gives general insight into the diversification of APD moieties of natural PBDs and provides proof-of-principle for precursor directed and combinatorial biosynthesis of new PBD-based antitumor compounds.
Keywords: farmaceutická chemie; molekulární struktura; Benzodiazepines; benzodiazepiny; Molecular Structure; Pyrroles; biologické přípravky; Chemistry, Pharmaceutical; protinádorové látky; benzodiazepinony; Benzodiazepinones; pyrroly; Antineoplastic Agents; Biological Products